Anticonvulsant Effect of Diazoxide against Dichlorvos-Induced Seizures in Mice. (17th December 2013) - Jazayeri, Amin; Zolfaghari, Samira; Ostadhadi, Sattar
Abstract : Dichlorvos, a synthetic organophosphate toxin, is used as pesticides. These toxins can be used as pesticides in farming and medicine for the devastation and/or elimination of ectoparasites of animals. Reports have shown that Dichlorvos generate seizure effects in various animals. Potassium channel opener is extensively used for medication of cardiovascular and other diseases. Studies have shown that potassium channel opener has anticonvulsant effects in different animal models. The goal of this study was to evaluate the effect of dizoxide on Dichlorvos-induced seizures in mice. In this research, the animals received different doses of Diazoxide (1, 2.5, 5, 10, and 20 mg/kg b.wt.) intraperitoneally 30 min before intraperitoneal injection of Dichlorvos (50 mg/kg b.w.t). After Dichlorvos injection, latency of clones, severity of seizure, and finally death as the fate were investigated. Results showed that Diazoxide dose-dependently decreased the severity of Dichlorvos-induced seizures, so that Diazoxide at a dose of 5 mg (the lowest, P < 0.05 ) and 20 mg/kg b.wt. (the highest, P < 0.001 ) has anticonvulsant effects. Thus, our data suggest that diazoxide as ATP-sensitive potassium channels opener has anticonvulsant activity against dichlorvas-induced seizure.